(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
One of the most common pathologies of the middle ear is exudative otitis media (EOM), which is characterized by the accumulation of exudate in the cavities of the middle ear with gradual degenerative manifestations and leads to To conductive or mixed hearing loss. The low-symptom course of the disease, especially in childhood, affects the development of children’s speech, worsens learning abilities, indirectly influences on intellectual development and social adaptation and, ultimately, the quality of life of a person of any age [1, 2]. In Russia over 13 million Human suffers with various hearing impairments, about 1 million are children and, according to WHO, by 2020 their number will increase by 30%. More than 1 / 3 all cases of hearing loss and deafness are associated with dysfunction of the auditory tube (ET) [3]. data different authors, to 80–90% children experience at least one episode of ESO before school [4, 5]. IN various sources mentioned O three classical theories of the etiology and pathogenesis of ESO [6]. Thus, there is the concept of hydrops ex vacuo, proposed by Politzer, according to which due to formations negative pressure in cavities average ear on background block transudate is formed in the auditory tube (ET).